DEVELOPMENT OF DISEASE IN RESIDENTS OF UKRAINE IN HAND CONTAMINATED WATER (Municipal economy of cities. Series: «Economy science», 2013)
Analyzes the impact of the use of the Ukrainian population of unsafe drinking water in different areas. Propose solutions to problems of water purification using alternative processes that allow to improve the quality of purified water and reduce morbidity Ukraine